THE PRINCIPLE OF PROPORTIONALITY - Hovhannisyan, Gor (State and Law, 2022)
The methodically clean, rationally comprehensible handling of the principle of proportionality is a central difficulty of all public law. Against the background of the practical importance of the principle of proportionality, which can hardly be overestimated, the article explains the four steps of the proportionality test. Examples are used to show which aspects play a role here. The examination of the principle of proportionality requires a differentiated argumentation that takes into account the particularities of the case. In this sense, the article provides guidance for the understanding and structured examination of the principle of proportionality. Based on numerous examples, the individual points of examination are explained and assistance for conclusive argumentation is shown. A concept is presented and specified on the basis of new research results, with the help of which the weighing process, which is often perceived as difficult, can be rationally structured. The paper also provides important basic knowledge on the recent discussion on proportionality.
Keywords: the principle of proportionality; legitimate objective; legitimate means; suitability; necessity; commensurability; weighing